Elie Wiesel – jøde – overlevende – menneske - Eitinger, Leo (Nordisk judaistik, 1988)
As many other survivors, Elie Wiesel wanted the world to know what had taken place in the concentration camps. At the same time, however, he felt that these experiences and the victims of the crimes were sacred in a mystical way and should not be profaned by mere description. It was only a series of peculiar circumstances that made him write his first book, The Night. Without knowing it, Wiesel by writing that book started a rescue operation for the survivors of the Nazi camps. Through his books, Wiesel gave their suffering a new meaning and their lives a new content. The history of the world and the Jewish people must not and in despair or indifference.